The Analysis of Mathematical Creative Thinking Skill and Independence in Problem-Based Learning With the Open-Ended Approach - Nurcholifah, Siti; Mastur, Zaenuri; Dwijanto, Dwijanto (Universitas Negeri Semarang, 2021)
The 21st century learning is required to develop 4C capabilities and one of them is creativity. The society that is with the rapid development of information technology needs critical, collaborative, communicative and creative thinking skills. This study aims to determine the characteristics of students' mathematical creative thinking skills in solving mathematical problems in the terms of independence in problem-based learning with the Open-Ended approach. The population in this study was class VII SMP Negeri 14 Semarang. The sampling in this study used cluster random sampling technique. The data obtained from tests of mathematical creative thinking skills, interviews and students’ learning independence questionnaires. The conclusion of this study is the independence of student learning in problem-based learning with the Open Ended approach has an influence on the ability to think creatively in mathematics.